2008
DOI: 10.1155/2008/749204
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Self-Paced Brain Computer Interface on Data Contaminated with Eye-Movement Artifacts and on Data Recorded in a Subsequent Session

Abstract: The performance of a specific self-paced BCI (SBCI) is investigated using two different datasets to determine its suitability for using online: (1) data contaminated with large-amplitude eye movements, and (2) data recorded in a session subsequent to the original sessions used to design the system. No part of the data was rejected in the subsequent session. Therefore, this dataset can be regarded as a “pseudo-online” test set. The SBCI under investigation uses features extracted from three specific neurologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…The present study showed that ECoG recordings provide high quality data for analysis with specific algorithm software. This is one of the major findings of this study compared to previous studies presenting different BCI systems based on recordings of ECoGs over several days but not a year, as in the study by Blakely that related a control of 7 days of implantation or EEG signals with acute experiments each day, but not long‐term .…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The present study showed that ECoG recordings provide high quality data for analysis with specific algorithm software. This is one of the major findings of this study compared to previous studies presenting different BCI systems based on recordings of ECoGs over several days but not a year, as in the study by Blakely that related a control of 7 days of implantation or EEG signals with acute experiments each day, but not long‐term .…”
Section: Discussionmentioning
confidence: 54%
“…Experimental Set Up The present study showed that ECoG recordings provide high quality data for analysis with specific algorithm software. This is one of the major findings of this study compared to previous studies presenting different BCI systems based on recordings of ECoGs over several days but not a year, as in the study by Blakely (32) that related a control of 7 days of implantation or EEG signals with acute experiments each day, but not long-term (33)(34)(35)(36)(37). This first step on rodents gave us a lot of information for future BCI experiments: Brain ECoGs can be used up to one year, they are stable, usable for data processing during one year, the performances of this BCI system in offline analysis were high (67.82% of True Positive Rate with a small 2.17 false positive/minute) and our results show encouraging data for the online use of this BCI (control of the effector by mental task).…”
Section: Experimental Design For Ecog Recordingmentioning
confidence: 53%
“…Although some studies have clearly shown that artefacts affect the performance of pure self-paced BCI systems [ 10 , 11 ], little attention has been paid to handle artefacts so far.…”
Section: Introductionmentioning
confidence: 99%
“…For the categorization, these papers have been combined and are represented by just one of the articles. Fatourechi et al [75,76] and Fatourechi, Ward, and Birch [53] all discuss the p o s t -p r o c e s s i n g i n b c i l i t e r a t u When systems use multiple methods, they are repeated for each.…”
Section: E T H O D C a T E G O R I Z A T I O N A N D O V E R V I E Wmentioning
confidence: 99%
“…Cooldown Fatourechi, Ward, and Birch [53] decreased their false positive rates with an average of 6% by adding a short cooldown period of only 1 decision sample, while reducing the true positive rate by just 1%. Verschore et al [63] decreased the necessary number of repetitions from 12 to only 2.69 on average.…”
Section: Adaptive Thresholdmentioning
confidence: 99%